Overcoming the Divide: An Interpretive Exploration of Young Black South Africans’ Lived Experiences of Upward Mobility in Central South Africa - Kok, Michael; Coetzee, Jan K.; Elliker, Florian (Qualitative Sociology Review, 2017)
The institutionalized racism that once subjugated the Black majority during South Africa’s apartheid years gave way after 1994 to legislature that aims to bring the country into a new era of egalitarianism. A striking result of this has been the steady flow of young Black people achieving upward mobility and making the transition into the middle- and upper-classes. This article explores young Black South Africans’ lived experiences of upward mobility, as well as their efforts to negotiate between separate and often contrasting identities by applying an interpretive sociological framework to their narrative accounts.